2020
DOI: 10.1163/1876312x-bja10002
|View full text |Cite
|
Sign up to set email alerts
|

A review of the biology and biogeography of Mantispidae (Neuroptera)

Abstract: Adult Mantispidae are general predators of arthropods equipped with raptorial forelegs. The three larval instars display varying degrees of hypermetamorphic ontogeny. The larval stages exhibit a remarkable life history ranging from specialised predators of nest-building hymenopteran larvae and pupa, to specialised predators of spider-eggs, to possible generalist predators of immature insects. Noteworthy advances in our understanding of the biology of Mantispidae has come to light over the past two decades whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 100 publications
0
17
0
Order By: Relevance
“…It has previously been reported that some species of Anchieta mimic stingless bees (Penny, 1982;Penny & Costa, 1984;Hogue, 1993), social wasps (e.g., A. fumosella in Buys, 2008) or braconids equipped with repugnant glands (e.g., A. fasciatella in Ardila-Camacho & García, 2015). Aggressive social paper wasps are common models for mantispids throughout the world (Batra, 1972;Boyden, 1983;Beck, 2005;Snyman et al, 2020), and individual species have been shown to form distinct color morph mimics that traces the local wasp fauna through polymorphism (Batra, 1972;Opler, 1981). While a Vespidae wasp model is observed in a single species (i.e., yellow and black morph of A. fumosella), most species of Anchieta appear to closely resemble either Ptilotrigona Moure, 1951 (e.g., A. apiculasaeva Thouvenot, 2009, A. bella , A. eurydella , A. partheniella , A. remipes (Gerstaecker, 1888), and Anchieta sp.…”
Section: Mimickingmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been reported that some species of Anchieta mimic stingless bees (Penny, 1982;Penny & Costa, 1984;Hogue, 1993), social wasps (e.g., A. fumosella in Buys, 2008) or braconids equipped with repugnant glands (e.g., A. fasciatella in Ardila-Camacho & García, 2015). Aggressive social paper wasps are common models for mantispids throughout the world (Batra, 1972;Boyden, 1983;Beck, 2005;Snyman et al, 2020), and individual species have been shown to form distinct color morph mimics that traces the local wasp fauna through polymorphism (Batra, 1972;Opler, 1981). While a Vespidae wasp model is observed in a single species (i.e., yellow and black morph of A. fumosella), most species of Anchieta appear to closely resemble either Ptilotrigona Moure, 1951 (e.g., A. apiculasaeva Thouvenot, 2009, A. bella , A. eurydella , A. partheniella , A. remipes (Gerstaecker, 1888), and Anchieta sp.…”
Section: Mimickingmentioning
confidence: 99%
“…Their general appearance superficially resembles that of praying mantises (Insecta: Mantodea), but such condition is evidently a product of evolutionary convergence (Aspöck & Aspöck, 2007). Despite the interesting morphology of the adults, the mimicry with toxic or poisonous insects exhibited by several genera, and the complex postembryonic development (hypermetamorphis) (Brauer, 1852(Brauer, , 1869(Brauer, , 1887 -in which their larvae may be ectoparasitoids, parasites, and spider-egg predators -, many aspects of mantidflies biology and taxonomy still need research (Redborg & MacLeod, 1985;Eggleton & Belshaw, 1992;Redborg, 1998;Snyman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With nearly 6000 extant species, Neuroptera is the largest and best-known order of Neuropterida (Vasilikopoulos et al 2020;Lu & Liu, 2021;Oswald, 2021), its adults characterized by gracile bodies and membranous, many-veined wings (Lu & Liu, 2021), many of them resembling insects of other groups, such as the extinct butterfly-like adults of Kalligrammatidae (Labandeira et al 2016;Liu et al 2018a), extant dragonfly-like adults of Ascalaphidae (Gao et al 2018), and mantis or wasp-like adults of Mantispidae (Snyman et al 2020). Compared with adults, neuropteran larvae are less prominent and have received less attention (Tauber et al 2009); however, they play an important role in the study of lacewing phylogeny (Aspöck & Aspöck, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mantis lacewings are representatives of Neuroptera (i.e., lacewings and their relatives). Neuroptera today comprise about 6,000 species worldwide (Engel et al 2018, Snyman et al 2020, Ardila-Camacho et al 2021. Mantispidae are classified within the larger group Mantispoidea, which aside from mantis lacewings also includes the groups Rhachiberothidae (thorny lacewings) and Berothidae (beaded lacewings), as well as extinct groups such as Mesoberothidae and Dipteromantispidae (Ardila-Camacho et al 2021).…”
Section: Introductionmentioning
confidence: 99%